2021
DOI: 10.1111/grow.12472
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between China's income inequality and transport infrastructure, economic growth, and carbon emissions

Abstract: Since the beginning of the 21st century, accompanied by the tremendous achievements of China's economic growth is an increasingly severe income gap between the rich and the poor. Based on panel data from 2000 to 2018, this study systematically examined the relationship among transport infrastructure, economic growth, carbon emissions, and income inequality in China, using the panel vector autoregressive model estimated by the generalized method of moments. We further divided China into three regions to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Consequently, long run has larger impact transport-carbon emission rather than short run. Former studies (e.g., Song 2021 ; Poi et al 2021 ; Feng et al 2021 ; Zhang and Zhang 2021 ) also confirm our findings that income inequality negatively associated with carbon emissions. However, their research concentrates merely on total carbon dioxide emissions rather than specific sector.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Consequently, long run has larger impact transport-carbon emission rather than short run. Former studies (e.g., Song 2021 ; Poi et al 2021 ; Feng et al 2021 ; Zhang and Zhang 2021 ) also confirm our findings that income inequality negatively associated with carbon emissions. However, their research concentrates merely on total carbon dioxide emissions rather than specific sector.…”
Section: Resultssupporting
confidence: 89%
“…This suggests that income inequality stimulates the economic activities, because, small portion of income is possessed by a few people or entities, which can be invested in productive projects within or across the countries. Moreover, higher income class has the potential to innovate new technology related to transport by spending on research and development concern over environmental quality (Hussain et al 2021 ; Wang et al 2020a , b , c ; Zhang and Zhang 2021 ; Yan and Yang 2021 ). The short-run outcomes also confirm income inequality is negatively associated with transport-carbon emissions across the OECD countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that income inequality significantly promotes direct CO 2 emissions under all quantile levels, and the impact on indirect CO 2 emissions is not significant. Zhang and Zhang [15] found that there is a long-run positive relationship between income inequality and carbon emissions in China.…”
Section: Literature Reviewmentioning
confidence: 99%